2019
DOI: 10.1253/circj.cj-18-1245
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Insight Into the Mechanisms of Cardiac Dysfunction in Patients With Type 1 Diabetes Mellitus Using Layer-Specific Strain Analysis

Abstract: Background: Although the subclinical left ventricular (LV) dysfunction caused by diabetes mellitus (DM) results in a high risk of death and heart failure, the details of cardiac dysfunction across a wide age range remain unclear. The aim of this study was to assess LV dysfunction in patients with type 1 DM (T1DM) using layer-specific strain analysis by echocardiography. Methods and Results: The 52 patients (median age: 23 [range: 5-40] years) with T1DM were divided into 3 age groups (D1: 5-14 years, D2: 15-24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In a previous study, we reported that LV longitudinal and circumferential strain at the basal level were useful and sensitive indicators of cardiac dysfunction caused by T1DM compared with the conventional parameters 42 . Further studies are needed to determine which parameters are useful as early and accurate indicators of cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a previous study, we reported that LV longitudinal and circumferential strain at the basal level were useful and sensitive indicators of cardiac dysfunction caused by T1DM compared with the conventional parameters 42 . Further studies are needed to determine which parameters are useful as early and accurate indicators of cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, this may reflect the young age of the participants and the short duration of the disease in our study as well as the fact that their diabetes appeared to be under fairly good control. As an indicator of short‐term hyperglycemia, HbA1c cannot show the relationship between glycemic control and cardiac function in diabetic patients with long disease durations 42 …”
Section: Limitationsmentioning
confidence: 99%
“…Subclinical systolic dysfunction was predominantly assessed using 2D STE parameters: GLS was measured in most of the cases, but global circumferential (GCS) and radial (GRS) strains were also measured in some of the included studies 4,7,8,16,21‐25 (Table 1). Furthermore, few studies also used 3D STE 1,7,26 and multiple‐layer strain 5,8,21,27‐30 for systolic function assessment. Systolic dysfunction was correlated with lower absolute values of GLS, GCS or GRS, 4,7 GLS being independently associated with cardiovascular events, short‐ and long‐term hospital mortality, all‐cause death and hospitalization 1,5,14,17,18,21,31‐33 .…”
Section: Resultsmentioning
confidence: 99%
“…A second mechanism could be related to cardiac hypertrophy, one of the first structural changes in the diabetic cardiomyopathy [22]. Insulin resistance, hyperactivity of the sympathetic system and hyperinsulinemia were all linked to cardiac hypertrophy [23]. Altered IVRT may be a precocious alteration in the development of cardiac hypertrophy [24].…”
Section: Plos Onementioning
confidence: 99%